Impact of Antiviral Treatment on Survival in HBV-Related Intrahepatic Cholangiocarcinoma Patients After Hepatectomy: A 14-Year Retrospective Follow-Up Study Based on the Propensity Score Matching Method - Chen Z; Zhang H; Zhang L; Han G; Zhang Y; Wu J; Li X; Mu X; Wang X (Therapeutics and Clinical Risk Management)
Zhiqiang Chen,* Hui Zhang,* Long Zhang, Guoyong Han, Yao Zhang, Jindao Wu, Xiangcheng Li, Xiaoxin Mu, Xuehao Wang Hepatobiliary Center, The First Affiliated Hospital of Nanjing Medical University, Key Laboratory of Liver Transplantation, Chinese Academy of Medical Sciences, NHC Key Laboratory of Hepatobiliary Cancers, Nanjing, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xuehao Wang; Xiaoxin Mu, Hepatobiliary Center, The First Affiliated Hospital of Nanjing Medical University, Key Laboratory of Liver Transplantation, Chinese Academy of Medical Sciences, NHC Key Laboratory of Hepatobiliary Cancers, Nanjing, Jiangsu, People’s Republic of China, Email wangxh@njmu.edu.cn; mux@njmu.edu.cnPurpose: Hepatitis B virus infection is one of the most common risk factors leading to the development of intrahepatic cholangiocarcinoma (ICC). This study aims to determine the impact of antiviral treatment (AVT) on the survival outcomes of ICC patients with hepatitis B virus infection.Patients and Methods: This retrospective study included ICC patients who had HBV infection and underwent hepatectomy from May 2009 to June 2023 at a single medical center. Patients’ baseline characteristics were analyzed, and the 14-year follow-up data were investigated using Kaplan-Meier curves and multivariable Cox proportional hazards regression models. The propensity score matching method was performed to balance the baseline differences between the AVT group and the non-AVT group.Results: A total of 229 patients were finally enrolled in the analysis. In the total cohort, 81 patients were classified into the AVT group and 148 patients into the non-AVT group. Kaplan-Meier curves showed that the AVT group exhibited prolonged overall survival and recurrence-free survival compared to the non-AVT group. Cox proportional hazards regression models revealed that AVT was an independent prognostic factor for both overall survival (HR 0.453, 95% CI: 0.280– 0.732) and recurrence-free survival (HR 0.659, 95% CI: 0.436– 0.997). A 1:1 nearest-neighbor matching algorithm was adopted, and 64 pairs of AVT and non-AVT patients were included in the propensity score matching cohort. Multivariable survival analyses confirmed AVT as a significant predictor for a favorable overall survival (HR 0.277, 95% CI: 0.147– 0.519), but no statistical significance for recurrence-free survival was observed between the AVT group and the non-AVT group after propensity score matching.Conclusion: We analyzed the long-term follow-up data for ICC patients with hepatitis B virus infection who underwent hepatectomy. Notably, AVT exhibited a beneficial impact on overall survival for these postoperative ICC patients. However, our findings indicated no statistically significant effect of AVT on recurrence-free survival.Keywords: intrahepatic cholangiocarcinoma, antiviral treatment, overall survival, recurrence-free survival, propensity score matching